Characteristics of BRAFV600E Mutant, Deficient Mismatch Repair/Proficient Mismatch Repair, Metastatic Colorectal Cancer: A Multicenter Series of 287 Patients. (31st May 2019) - de la Fouchardière, Christelle; Cohen, Romain; Malka, David; Guimbaud, Rosine; Bourien, Héloïse; Lièvre, Astrid; Cacheux, Wulfran; Artru, Pascal; François, Eric; Gilabert, Marine; Samalin‐Scalzi, Emmanuelle; Zaanan, Aziz; et al.
Abstract: Background: BRAF V600E mutations occurring in about 10% of metastatic colorectal cancers (mCRCs) are usually associated with a poor outcome. However, their prognostic factors are unknown. Materials and Methods: We built a multicenter clinico‐biological database gathering data from patients with BRAF V600E ‐mutant mCRC treated in one of the 16 French centers from 2006 to 2017. The primary endpoint was to identify prognostic factors using a Cox model. Results: We included 287 patients (median age, 67 years [28–95]; female, 57%). Their median overall survival was 20.8 months (95% confidence interval [CI], 17.97–27.04), and median progression‐free survival in the first‐line setting was 4.34 months (95% CI, 3.81–5.03). Chemotherapy regimen and biological agents (antiangiogenic or anti‐epidermal growth factor receptor) were not associated with overall and progression‐free survival. Stage IV disease (synchronous metastases) and absence of curative‐intent surgery were statistically associated with poor overall survival. Among the 194 patients with mismatch repair (MMR) status available, overall survival was significantly longer in patients with deficient MMR tumors compared with those with proficient MMR tumors (adjusted hazard ratio = 0.56; p = .009). Conclusion: Despite that BRAF V600E ‐mutant mCRCs are associated with poor overall and progression‐free‐survival, patients with deficient MMR tumors and/or resectable disease experienced a longer survival. These results highlight the importance of MMR testing and resectability discussion in patients with BRAF V600E mCRC in day‐to‐day practice. Implications for Practice: Mismatch repair (MMR) testing and resectability discussion in patients with BRAF V600E metastatic colorectal cancer (mCRC) should be performed in day‐to‐day practice to steer treatment decision making in patients with BRAF V600E ‐mutant mCRC. Abstract : This article describes the real‐life management of BRAF V600E ‐mutant metastatic colorectal cancer in a large cohort of patients treated in 16 French centers from 2006 to 2017. Potential prognostic factors to steer treatment decisions are identified. Abstract : 摘要 背景。 在转移性结直肠癌 (mCRC) 病例中，约发生10% 的 BRAF V600E 突变，通常与不良预后有关。然而，影响预后的因素尚未可知。 材料和方法。 我们建立了一个多中心临床生物学数据库，旨在收集 2006 年至 2017 年在法国 16 家中心中任意一家治疗的 BRAF V600E 突变型mCRC患者的数据。主要目的是利用 Cox 模型确定影响预后的因素。 结果。 我们纳入了 287 名患者 [平均年龄 67 岁 (28–95)；女性占 57%]。他们的中位总生存期为 20.8 个月 [95% 置信区间 (CI)，17.97–27.04]，在一线治疗中，中位无进展生存期为 4.34 个月(95% CI，3.81–5.03)。化疗方案和生物制剂(抗血管生成或抗表皮生长因子受体)与总生存期和无进展生存期无关。在统计学上，癌症四期(同步转移)和无根治性手术与较短的总生存期有关。在 194 名存在错配修复 (MMR) 状态的患者中，相较于MMR完整的肿瘤患者，MMR缺陷肿瘤患者的总生存期明显较长(校正风险比 = 0.56； p = .009)。 结论。 尽管 BRAF V600E 突变型mCRC可导致较短的总生存期和无进展生存期，但MMR缺陷肿瘤患者和/或可切除病灶的患者生存期更长。这些结果表明，在日常临床实践中，MMR检测和可切除性讨论对于 BRAF V600E 突变型mCRC患者至关重要。 实践意义: 在日常实践中，应针对 BRAF V600E 突变型转移性结直肠癌患者 (mCRC) 进行错配修复 (MMR) 检测和开展可切除性讨论，以指导 BRAF V600E 突变型mCRC患者的治疗决策。